RoboTable: An Infrastructure for Intuitive Interaction with Mobile Robots in a Mixed-Reality Environment - Haipeng Mi; Aleksander Krzywinski; Tomoki Fujita; Masanori Sugimoto (Advances in Human-Computer Interaction)
This paper presents the design, development, and testing of a tabletop interface called RoboTable, which is an infrastructure supporting intuitive interaction with both mobile robots and virtual components in a mixed-reality environment. With a flexible software toolkit and specifically developed robots, the platform enables various modes of interaction with mobile robots. Using this platform, prototype applications are developed for two different application domains: RoboPong investigates the efficiency of the RoboTable system in game applications, and ExploreRobot explores the possibility of using robots and intuitive interaction to enhance learning.